Implementation of Quality Assurance Management Basic Education (PAUD) in Indonesia - Iin Kusmawati; R. Madhakomala (East Asian Journal of Multidisciplinary Research, 2023)
Early childhood education has a strategic role in human development. Therefore, quality education is needed. This study aims to determine the implementation of Early Childhood Care and Education (ECCE) / (PAUD) quality assurance management in Indonesia. A qualitative approach is carried out using the literature review method. The results show that implementing primary education quality control (ECCE) in Indonesia is crucial in ensuring a bright future for Indonesian children. In addition to the External Quality Assurance System, such as accreditation is also known as the Internal Quality Assurance System. Until now, SPMI has only been carried out at the Primary and Secondary Education and Higher Education levels. Until now, quality assurance has only been managed externally at the ECCE level, namely through BAN PAUD. As for the PAUD unit itself, there is no formal legal oversight of the implementation of SPMI. So we can see how the quality of ECCE in Indonesia until now is still very far from expectations.